Third Hankel Determinant for the Inverse of Starlike and Convex Functions (Communications in Mathematical Research, 2019)
Denote $\cal S$ to be the class of functions which are analytic, normalizedand univalent in the open unit disk $\mathbb U=\{z\colon |z|